Influence of emotions on clinical performance in acute care: A scoping review - Cheng En Xi; Sylvain Boet; Alexandre Assi; Lindsey Sikora; Meghan M. McConnell (PLoS ONE, 2025)
Acute care is a high stake, emotionally charged environment. Although emotions are increasingly recognized as integral to various aspects of healthcare, research examining how they influence and interact with clinical performance in acute care settings remains relatively limited. This scoping review aims to summarize relevant empirical research on the influence of emotions on clinical performance in acute care settings. The following databases were searched by a health sciences librarian: Medline and Medline in Process, Embase Classic and Embase, Cochrane’s CENTRAL, APA PsycINFO, CINAHL, and ERIC, from inception to June 2024. Empirical research in English related to the effect of emotions on clinical performance in acute care settings were included. The screening was conducted in duplicate independently, and data extraction was done by the lead author and reviewed by a second author. Among 6430 references assessed, 22 studies were analyzed. Three themes were identified based on the research setting: simulated/educational acute care settings, real-world acute care settings, and end-of-life care settings. Overall, negative emotions, most commonly stress, were inversely correlated with clinical performance in some simulated or educational settings and discouraged patient contact in real clinical settings, while positive emotions encouraged more comprehensive care. Experiencing fear and uncertainty led to more cautious care decisions, and negative emotions associated with patient’s families were prevalent in end-of-life care. Emotions had varying effects on clinical performance and decision-making in acute care settings, depending on the types of emotions and the clinical contexts. More research is needed to find strategies to help clinicians manage those emotions.